Women’s Political Participation - Researcher with a Female Respondent in an interview in Nairobi - Ademola-Adeoye, Feyisayo (Locating the Albatross in Women's Political Participation in Sub-Saharan Africa, 2021)
Video of the main study recorded in Nairobi, Kenya
Keywords: Women; Sub-Saharan Africa; Political rights; Political participation; Structural Barriers; Political Barriers; Politics